Knowledge of Circular Economy among Waste Managers in Benin Metropolis, Edo State - Igudia, Efetibhor; Ibhazobe, Lawrence (NIU Journal of Management Sciences; Vol 12 No 2 (2026): NIU Journal of Management Sciences, Vol. 12, No. 2, June 2026, 2026)
This research investigated the knowledge of circular economy among waste managers in Benin Metropolis, Edo State, Nigeria. The descriptive survey research design was adopted. The population consisted of 480 waste managers operating within the 3 Local Government Areas that make up Benin Metropolis. A basic random sampling procedure was used to pick a sample of 259 respondents. A 30-item circular economy knowledge exam and a self-created structured questionnaire were used to gather data. According to Cronbach Alpha statistics, the instrument's reliability coefficient was 0.71. Analysis of Variance (ANOVA), mean, standard deviation, percentages, and the independent samples t-test at the 0.05 level of significance were used to examine the data. The result revealed that the majority of waste managers possessed a moderate degree of familiarity with the concepts of the circular economy. The study further showed that knowledge of circular economy did not significantly differ based on educational level, age group, or gender of waste managers. The study concluded that waste managers generally possessed similar levels of knowledge of circular economy irrespective of demographic characteristics. The study recommended the implementation of formal and informal environmental education programmes, increased public sensitization campaigns, and strengthened stakeholder involvement in promoting circular economy practices among waste managers and the general public. Keywords: Circular Economy, Waste Management, Recycling, Environmental Education, Waste Managers, Benin Metropolis.